Confronting astrophysical uncertainties in the direct detection of dark matter - Kavanagh, Bradley James (2014)
The detection of dark matter (DM) by direct detection experiments has great potential to shed light on particle physics beyond the Standard Model. However, uncertainties in the DM speed distribution f1(v) may lead to biased reconstructions of particle physics parameters, such as the DM mass and interaction cross sections. In this work, we aim to determine whether these parameters can be determined from future direct detection data without any prior assumptions about f1(v).